Addition of Hydrogen in Spark Ignition Engine Combustion Process: A Review - Andi Ibrahim Soumi; Dessy Ade Pratiwi; Ummi Kultsum; Rouf Muhammad (Creative Research in Engineering (CERIE), 2024)
The increasing consumption of fossil energy causes fossil energy reserves to become depleted and pollutants in the environment increase. One approach to decreasing reliance on fossil fuels is through the use of renewable energy sources. Hydrogen can serve as a substitute fuel option. One of the uses of hydrogen as a renewable fuel is as an addition to gasoline combustion engines. This study includes a review of previous research on the addition of HHO to gasoline engines on the parameters of power, torque, specific fuel consumption, thermal efficiency, and exhaust emissions. The results of a review of previous studies show that the addition of HHO to gasoline engines can increase engine output power, torque, and thermal efficiency and can reduce combustion exhaust emissions and the addition of hydrogen can reduce specific fuel consumption.